Complete Python course with 10 real-world projects. (Packt Publishing, 2023)
Python is a multi-paradigm programming language with object-oriented and structured programming fully supported, and many features support functional and aspect-oriented programming (metaprogramming and metaobjects). Several other paradigms are supported through extensions, including design by contract and logical programming. This course begins with a brief introduction and covers basic to advanced programming techniques in Python. The first 12 sections of the course cover Python basics. The remaining sections cover intermediate to advanced Python concepts (OOPS, classes, lists, modules, functions, JSON, and so on). Learn to use Matplotlib, NumPy, Flask, and Android APK files. Learn database handling and build geographical apps. The ten buildable apps covered in the course include a volcano web map generator, object detector app, personal website built with Python and Flask, book inventory desktop GUI app with SQL backend, data analysis/visualization dashboard, mobile app on Android and iOS devices, an app that scrapes multiple real estate webpages data, web app to collect user data and sends emails, blog and translator with Django, and web app to process Excel files and download processed files. Upon completion, you can create executable Python programs independently and master coding syntax and Python comprehensively. What You Will Learn Develop an understanding of object-oriented programming in Python Learn how to use various Python libraries and frameworks Learn to create desktop programs, web/data apps, APIs, web scrapers Learn other programming tools like SQL, HTML, deployment, and debug Explore how to use JSON, CSV, Excel, NumPy, and Android APK files Learn data analysis and visualization with Matplotlib and PostgreSQL Audience The course exclusively delivers content for people who have not programmed before and assumes you have no previous programming knowledge. You will learn every programming concept in the context of real-life programming examples by building real-world programs. If you are a budding programmer looking to acquire comprehensive programming skillsets using Python language or are looking to master Python coding, this course is for you. The prerequisites include accessing a computer (Windows, Mac, or Linux). No prior knowledge of Python or previous programming experience is needed. About The Author PythonHow: Ardit Sulce is a Python programmer, teacher, and founder of PythonHow. He graduated in 2013 with a master's degree in science (geospatial technologies) from the University of Muenster in Germany, focusing on using Python for remote sensing. Ardit has worked with companies such as the Center for Conservation Geography to map and understand Australian ecosystems, image processing with the Swiss in-Terra, and data mining to gain business insights with the Australian Rapid Intelligence.